Endocrine correlates of partner preference behavior in rams - Resko, J.A. (Oregon Health Sciences University, Portland, OR.); Perkins, A; Roselli, C.E; Fitzgerald, J.A; Choate, J.V.A; Stormshak, F (Biology of reproduction, 1996)
We studied a unique group of rams that would not mate with estrous ewes during extensive testing for sexual behavior. The same rams courted males in preference to females in 30-min sexual preference tests and were classified as male-oriented (n = 6). We compared the following endocrine profiles: systemic steroid concentrations, the capacity of the testes to biosynthesize 17alpha-hydroxyprogesterone and testosterone from 3H-progesterone in vitro, and the levels of brain aromatase activity (AA) in male-oriented rams vs. rams that were proven breeders and designated as female-oriented (n = 7). After the last behavioral test, sera were collected, and males in each experimental group were killed. Brains and testes were obtained for subsequent determinations of AA and measurements of steroidogenic enzyme activity. All dissections and subsequent assays were performed without knowledge of experimental group assignments. Serum concentration of testosterone (T), dihydrotestosterone (DHT), androstenedione, estrone (E1), and estradiol-17beta (E2) were determined by RIA. AA was quantified by a 3H2O assay validated for neural tissue of the ram. We studied frontal, parietal and cingulate cortex, cerebellum, hippocampus, olfactory bulb, septum, amygdala, infundibulum-median eminence, and preoptic area (POA). Serum T, E1, and E2 concentrations of female-oriented subjects were significantly higher (p 0.05) than those in male-oriented subjects (SEM: 1559 +/- 228, 46 +/- 2, and 15 +/- 3 pg/ml vs. 874 +/- 196, 40 +/- 2, and 8 +/- 1 pg/ml serum, respectively). DHT and androstenedione concentrations in the systemic circulation did not differ between groups